The costs of favoritism: is politically-driven aid less effective? - Dreher, Axel (Discussion papers, 2010)
As is now well documented, aid is given for both political as well as economic reasons. The conventional wisdom is that politically-motivated aid is less effective in promoting developmental objectives. We examine the ex-post performance ratings of World Bank projects and generally find that projects that are potentially politically motivated - such as those granted to governments holding a non-permanent seat on the United Nations Security Council or an Executive Directorship at the World Bank - are no more likely, on average, to get a negative quality rating than other projects. When aid is given to Security Council members with higher short-term debt, however, a negative quality rating is more likely. So we find evidence that World Bank project quality suffers as a consequence of political influence only when the recipient country is economically vulnerable in the first place.